Connaissance indigène des procédés de production du beurre de Pentadesma butyracea Sabine au Bénin - Aïssi, MV.; Sogbégnon, RA.; Natta, AK.; Soumanou, MM. (Tropicultura, 2015)
Indigenous Knowledge on Production Processes of Pentadesma butyracea Sabine Butter in Benin. Pentadesma butyracea Sabine is a tree that produces fruits containing oleaginous seeds from which butter, similar to shea butter, is extracted. This butter, so far insufficiently known, is obtained traditionally by a poorly documented process. Based on a technological investigation in the rural area and a factorial correspondences analysis (FCA), this study contributes to a better knowledge of the traditional technology of the P. butyracea butter production in Benin. P. butyracea butter is extracted by twelve main successive unit operations. The transformers involved in the butter production belong to eight different ethnic groups. Two types of thermal pretreatments, namely cooking with water and roasting in a traditional furnace are applied to P. butyracea seeds. The influence of the ethnic group was reported, especially on the type of the thermal pretreatment applied to the seeds as well as the various unit operations of transformation implemented from fruit picking up to obtaining butter. This better knowledge will allow improving the traditional processes of the P. butyracea butter production in rural environment.